Awareness of the Risk of Paradoxical Psoriasis in Patients with SAPHO Syndrome Undergoing Treatment with Secukinumab: A Case Series - Xu C; Xu X; Han Y (Journal of Inflammation Research)
Cheng Xu,* Xiayan Xu,* Yongmei Han Department of Rheumatology, Sir Run Run Shaw Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yongmei Han, Department of Rheumatology, Sir Run Run Shaw Hospital, Zhejiang University School of Medicine, 3#Qingchun East Road, Hangzhou, 310016, People’s Republic of China, Email 3408235@zju.edu.cnAbstract: SAPHO syndrome is a systemic inflammatory disease characterized by skin lesions and inflammatory changes in the bones and joints. There is no consensus on the treatment strategy of SAPHO syndrome. For patients with refractory SAPHO syndrome, biological agents can be considered. We report three patients who responded poorly to conventional therapy, all of whom had paradoxical recurrence of pustulosis after receiving secukinumab, and whose paradoxical pustulosis resolved after adjustment to tofacitinib. We reviewed the literature and concluded that secukinumab may be potentially risky for the treatment of SAPHO syndrome. This paradoxical aggravation of the rash may be related to paradoxical psoriasis. The specific pathogenesis is not clear, and tofacitinib may be a remedy for this situation.Keywords: SAPHO, PPP, IL-17, secukinumab, paradoxical psoriasis